Associations Between Adverse Childhood Experiences and Trauma Among Young People Who Offend: A Systematic Literature Review. (December 2022) - Malvaso, Catia G.; Cale, Jesse; Whitten, Tyson; Day, Andrew; Singh, Sara; Hackett, Louisa; Delfabbro, Paul H.; Ross, Stuart
This systematic review synthesized current knowledge about the prevalence of adverse childhood experiences (ACEs) among young people known to have offended and examined evidence of associations between ACEs, trauma symptoms, and offending behavior. A systematic search of English-language, peer-reviewed studies published from the year 2000 onwards was conducted. A final pool of 124 studies that reported quantitative data were included in the review. The Cambridge Quality Checklist for the assessment of studies on offending was used to assess methodological quality of included studies. Pooled data indicated that almost 87% of justice-involved young people across 13 countries experienced at least one traumatic event. The odds of experiencing at least one ACE were over 12 times greater for justice-involved young people compared with nonjustice-involved young people. Prevalence of individual ACEs ranged from 12.2% for childhood sexual abuse to 80.4% for parental separation among justice-involved young people. Those who reported both a higher number and multiple types of ACEs were more likely to be diagnosed with post-traumatic stress symptoms. However, when considering only high-quality studies, there was minimal evidence to suggest that a higher incidence of ACEs predicted trauma symptoms or that trauma symptoms mediated the association between ACEs and offending behavior. Further research is needed to elucidate factors that differentiate young people exposed to ACEs who go on to offend from those who do not. This research is essential to understanding whether ACEs and trauma are drivers of offending behavior and for informing prevention and intervention strategies.